Signos banta ng nagbabagong klima - Gutierrez, Richard; Nuñez, Marilen Go; Gatchalian, Elmer; Severino, Howie; Pulido, Maki; Tina, Raffy (GMA News and Public Affairs, 2008)
This program features the most pressing environmental issue today -- the world's changing climate as a result of decades of unchecked human activity.